Endemic plants of tropical dry evergreen forest, Southern India - Balachandran, Natesan; Rajendiran, Krishnamurthy; Gastmans, Walter (Biodiversity: Research and Conservation, 2018)
During the last two decades of intensive botanical survey of the tropical dry evergreen forest, a total of 82 endemic taxa were found out of 1142 species enumerated from 85 sites in the three Coromandel Coastal districts of the state Tamil Nadu: Cuddalore, Kancheepurm and Villupuram, and in the Pondicherry district. Of 82 species, 17 are trees, 11 shrubs, 9 climbers and 45 herbs. Distribution of these endemic species was analyzed and categorised as endemic to the country, peninsular India, southern India, Eastern and Western Ghats, and at the state and district level. Interestingly, the study found that some endemic species were disjunctly distributed between districts, states, ghats, climatic regimes and bioregions. Anthropogenic disturbance and species threat status were also studied and discussed.